Designing clinical trials for assessing the effectiveness of interventions for tinnitus - Hall, Deborah A. (Sage, 2017)
In the face of finite resources, allocations of research and healthcare funding are dependent upon high-quality evidence. Historically, tinnitus has been the poor cousin of hearing science, with low-quality clinical research providing unreliable estimates of effect, and with devices marketed for tinnitus without strong evidence for those product claims. However, the tinnitus field is changing. Key opinion leaders have recently made calls to the field to improve the design, implementation and reporting of clinical trials, and there is growing intersectoral collaboration. The Tonndorf Lecture presented at the 1st World Tinnitus Congress and 12th International Tinnitus Seminar in Warsaw, Poland provided an opportunity to reflect on the present and future progress of tinnitus research and treatment and what is needed for the field to achieve success. The content of that lecture is summarised in this review article. The main debate concerns the selection and reporting of outcomes in clinical trials of tinnitus. Comprehensive reviews of the literature confirm the diversity of the personal impact of tinnitus, and illustrate a lack of consensus in what aspects of tinnitus should be assessed and reported in a clinical trial. An innovative project is described which engages the global tinnitus community (patients and professionals alike) in working together. This project seeks to improve future tinnitus research by creating an evidence-based consensus about minimum reporting standards for outcomes in clinical trials of a tinnitus intervention. The output will be a core set of important and critical outcomes to be measured and reported in all clinical trials.